Positive end-expiratory pressure (PEEP) level to prevent expiratory flow limitation during cardiac surgery: study protocol for a randomized clinical trial (EFLcore study) - Elena Bignami; Savino Spadaro; Francesco Saglietti; Antonio Di Lullo; Francesca Dalla Corte; Marcello Guarnieri; Giulio de Simone; Ilaria Giambuzzi; Alberto Zangrillo; Carlo Alberto Volta (Trials, 2018)
Abstract Background Lung dysfunction commonly occurs after cardiopulmonary bypass (CPB). Randomized evidence suggests that the presence of expiratory flow limitation (EFL) in major abdominal surgery is associated with postoperative pulmonary complications. Appropriate lung recruitment and a correctly set positive end-expiratory pressure (PEEP) level may prevent EFL. According to the available data in the literature, an adequate ventilation strategy during cardiac surgery is not provided. The aim of this study is to assess whether a mechanical ventilation strategy based on optimal lung recruitment with a best PEEP before and after CPB and with a continuous positive airway pressure (CPAP) during CPB would reduce the incidence of respiratory complications after cardiac surgery. Methods/design This will be a single-center, single-blind, parallel-group, randomized controlled trial. Using a 2-by-2 factorial design, high-risk adult patients undergoing elective cardiac surgery will be randomly assigned to receive either a best PEEP (calculated with a PEEP test) or zero PEEP before and after CPB and CPAP (equal to the best PEEP) or no ventilation (patient disconnected from the circuit) during CPB. The primary endpoint will be a composite endpoint of the incidence of EFL after the weaning from CPB and postoperative pulmonary complications. Discussion This study will help to establish a correct ventilatory strategy before, after, and during CPB. The main purpose is to establish if a ventilation based on a simple and feasible respiratory test may preserve lung function in cardiac surgery. Trial registration ClinicalTrials.gov, ID: NCT02633423. Registered on 6 December 2017.